ADDRESSING AN UNMET NEED FOR MENTAL HEALTH SUPPORT DURING CARE TRANSITIONS FROM NURSING FACILITIES. (8th November 2019) - Simons, Kelsey; Luci, Katherine; Hagemann, Lauren; Jacobs, M Lindsey; Bower, Emily; Eichorst, Morgan; Hilgeman, Michelle
Abstract: Mental health (MH) disorders are common among skilled nursing facility (SNF) residents and may inhibit rehabilitation goals. Moreover, discharges to the community from SNFs are periods of heightened suicide risk within the Veterans Health Administration (VHA), suggesting an urgent need for improved continuity of MH care. This paper presents results of medical records reviews indicating a potential gap in MH services at discharge from VHA SNFs. A quality improvement project ("Suicide Awareness for Veterans Exiting Community Living Centers" – SAVE-CLC), designed to address this gap, will also be discussed. Piloted in 3 sites (N = 66) in 2018, SAVE-CLC clinicians administered depression screens by phone to 47 Veterans (71%) after SNF discharge and helped connect Veterans to MH services. 24 Veterans (26%) received a second such call. Patients and caregivers expressed high satisfaction with SAVE-CLC (n = 35, 97%). Implications for quality improvements in SNF care transitions will be discussed.